Difficulties in diagnostics of genital tuberculosis - M. A. Andrianov; A. K. Davletova; T. E. Kurmanbaev; L. E. Albegova; E. T. Nurmukhametova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Genital tuberculosis is a specific lesion of the female genital organs by an infection caused by mycobacteria of the Mycobacteriaceae family. The disease is most often registered in reproductive age, the leading complaints are infertility, menstrual irregularities, pelvic pain. Diagnosis of tuberculosis of the female genital organs is a complex task: the absence of specific clinical symptoms, the duration of the course, as well as the low level of alertness of doctors and patients do not always allow for a timely diagnosis and the beginning of appropriate treatment. In addition, patients with infertility against the background of undiagnosed genital tuberculosis can be subjected to assisted reproductive technology procedures. In the article, we present a clinical example of a patient with secondary infertility against the background of tuberculous lesions of the uterine appendages demonstrating all of the above.